Option Value, Existence Value, and Bequest Value of Mangrove in Jerowaru District, Lombok Timur Regency, Nusa Tenggara Barat - Harry Irawan Johari; Sukuryadi Sukuryadi; Surya Hadi (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2023)
The value of mangroves is not only in the form of wood products, but can also be in the form of non-timber forest products (HHBK) and environmental services. Information is needed regarding the value of the importance of using mangroves in the future, the value of conserving their biodiversity, and the value of community appreciation for their existence. The research was conducted around of mangrove area in Jerowaru District, Lombok Timur Regency, Nusa Tenggara Barat Province from February – July 2022. The method used in this research is a quantitative approach through the provision of option values, existence values, and bequest values to mangroves which are determined based on estimates using WTP (willingness to pay), whose values are based on the contingent valuation approach. Based on the results of the assessment of the options benefit, the existence benefit, and the inheritance benefits, of mangroves in Jerowaru District, Lombok Timur Regency, Nusa Tenggara Barat Province, it is known that the value of the optional benefit related to biodiversity conservation for the benefit of utilization in the future is ± IDR 224,885.25/ha/year. The value of the existence benefit related to habitat continuity for user species ± IDR 84,953.96/ha/year and the value of the bequest benefit related to community appreciation of the ownership of resources ± IDR 1,066,667/ha/year